Fertility Preservation in Men with Cancer: Issues and Benefit of an Established Program - Mosley, Mary (MD Conference Express, 2014)
Cancer care has evolved to a focus on quality of life after treatment, in addition to survival, making fertility preservation (FP) a survivorship issue. This article reviews the success of integrating a formalized oncofertility program into acute cancer care and in improving the rates of FP.